pH-mediated potentiation of gallium nitrate against Pseudomonas aeruginosa - Liu, Chang; Cui, Chenxuan; Tan, Xiaoxin; Miao, Junjie; Wang, Wei; Ren, Han; Wu, Hua; Zheng, Cuiying; Ren, Huan; Kang, Weijun (Frontiers in Microbiology, 2024)
The emergence of multidrug-resistant Pseudomonas aeruginosa isolates is a growing concern for public health, necessitating new therapeutic strategies. Gallium nitrate [Ga(NO3)3], a medication for cancer-related hypercalcemia, has attracted great attention due to its ability to inhibit P. aeruginosa growth and biofilm formation by disrupting iron metabolism. However, the antibacterial efficacy of Ga(NO3)3 is not always satisfactory. It is imperative to investigate the factors that affect the bactericidal effects of Ga(NO3)3 and to identify new ways to enhance its efficacy. This study focused on the impact of pH on P. aeruginosa resistance to Ga(NO3)3, along with the underlying mechanism. The results indicate that acidic conditions could increase the effectiveness of Ga(NO3)3 against P. aeruginosa by promoting the production of pyochelin and gallium uptake. Subsequently, using glutamic acid, a clinically compatible acidic amino acid, the pH was significantly lowered and enhanced the bactericidal and inhibitory efficacy of Ga(NO3)3 against biofilm formation by P. aeruginosa, including a reference strain PA14 and several multidrug-resistant clinical isolates. Furthermore, we used an abscess mouse model to evaluate this combination in vivo; the results show that the combination of glutamic acid and Ga(NO3)3 significantly improved P. aeruginosa clearance. Overall, the present study demonstrates that acidic conditions can increase the sensitivity of P. aeruginosa to Ga(NO3)3. Combining glutamic acid and Ga(NO3)3 is a potential strategy for the treatment of P. aeruginosa infections.